46.5k views
4 votes
I don’t know how to do it can someone help me?

I don’t know how to do it can someone help me?-example-1
User Lmcadory
by
6.2k points

1 Answer

2 votes

Answer:f(g(0))= 1/5

g(f(0))= 7

Explanation:

for f(g(0))=you solve for g(x) but you plug in 0 for x so g(0)= 8(0)+3

=3

so now you plug in the answer of the function of g(x) witch is 3 and plug it in as the x for F(x) so f(3)= 1/(3)+2

= 1/5

so f(g(0)) is equal to 1/5

Now for G(f(0)) you solve for f(x) by pluging 0 for x so F(0)= 1/(0)+2

=1/2

now you plug in 1/2 for the x of g(x) so g(1/2)= 8(1/2)+3

= 4+3

=7

so g(f(0)) is equal to 7

Hope this helps:)

User Imjoymhnt
by
6.2k points